The “coactive procedure” in the ecuadorian legislation of the last years (2005-2018), and its regime in the organic administrative code - Serrano, Luis Adrian (2018)
The coercive procedure refers to the application of the administrative authority with respect to an obligation that citizens or foreigners contract for various circumstances in a given state; Regarding the administrative procedure, several legal bodies have determined its structure and procedural application. The Organic Administrative Code is imposed on the previous regulations to regulate at present this procedure that deserves an analysis regarding due process, the right to self-defense, legal security and its principles in general, to determine if it has managed to overcome the gaps procedural and legal that have been observed in previous laws. KEY WORDS: coercive procedure, legal security, effective judicial protection, due process, public administration. JEL CODE: H81, H83